(untitled) (Fiep Bulletin - online, 2015)
The objective of this study was to verify the effect of training on the anaerobic threshold (4 mM of blood lactate) (AT) and critical speed (CS) determined from different distances, in swimmers aged 13 to 15 years. Participated of this study 11 swimmers (6 girls and 5 boys), with 3 to 5 years of experience in the modality. Their physical characteristics were: age = 13.54 + 0.52 yr., body mass = 52.42 + 4.03 kg and stature = 1.60 + 0.06 m. The swimmers are involved in a training program 5 times per week with a mean week volume between 8000 and 20000 m, approximately. At was determined trough linear interpolation between speed and lactate concentration obtained in two submaximal repetitions of 200 m. For the determination of CS1 (25, 50 and 100 m), CS2 (50, 100 and 200 m) and CS3 (100, 200 and 400 m) different distances were used. Training consisted of 14 weeks contained in a macrocycle of 6 months, which corresponded to the specific (8 weeks) and competitive (6 weeks) periods. At two moments of training, CS1 and CS2 were significantly higher than CS3 and AT. There was an improvement in the performance (m/s) on the distances of 50 (1.40 + 0.12 and 1.45 + 0.13), 100 (1.25 + 0.13 and 1.32 + 0.14) and 200 m (1.12 + 0.13 and 1.18 + 0.13), and the speed (m/s) corresponding to CS1 (1.16 + 0.14 and 1.25 + 0.13) and CS2 (1.04 + 0.13 and 1.10 + 0.13), after training. Thus, in swimming, the distance used in the determination of CS interferes on its relationship with AT and response to training. When determined trough longer distances, CS have a similar behavior of AT after a specific training period.